2022
DOI: 10.3390/molecules27217413
|View full text |Cite
|
Sign up to set email alerts
|

Impact of TMPRSS2 Expression, Mutation Prognostics, and Small Molecule (CD, AD, TQ, and TQFL12) Inhibition on Pan-Cancer Tumors and Susceptibility to SARS-CoV-2

Abstract: As a cellular protease, transmembrane serine protease 2 (TMPRSS2) plays roles in various physiological and pathological processes, including cancer and viral entry, such as severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Herein, we conducted expression, mutation, and prognostic analyses for the TMPRSS2 gene in pan-cancers as well as in COVID-19-infected lung tissues. The results indicate that TMPRSS2 expression was highest in prostate cancer. A high expression of TMPRSS2 was significantly associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 49 publications
(57 reference statements)
0
5
0
Order By: Relevance
“…CTSL is another receptor for SARS-CoV-2 ( 57 ). Additionally, CD suppresses the expression of other SARS-CoV-2 receptors (e.g., FURIN and transmembrane serine protease 2), in different cancer cells ( 47 , 80 ). Evidence indicates that a large number of multinucleated cells characteristic of syncytial pathology are present in patients with COVID-19 ( 73 ).…”
Section: Discussionmentioning
confidence: 99%
“…CTSL is another receptor for SARS-CoV-2 ( 57 ). Additionally, CD suppresses the expression of other SARS-CoV-2 receptors (e.g., FURIN and transmembrane serine protease 2), in different cancer cells ( 47 , 80 ). Evidence indicates that a large number of multinucleated cells characteristic of syncytial pathology are present in patients with COVID-19 ( 73 ).…”
Section: Discussionmentioning
confidence: 99%
“…CD is an adenosine analog with wide pharmacological effects and maybe resistance to a variety of tumors ( 18 , 19 , 47 ) and viruses ( 48 50 ), including SARS-CoV-2 ( 20 , 29 , 51 , 52 ). We analyzed the role of CD in different tumor cells and found that CD concentration-dependently decreased SOX9 protein and mRNA expression in 22RV1, PC3, and H1975, suggesting that the anticancer effect of CD may be associated with SOX9 inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…All cells were cultured in a 37°C incubator with 5% CO 2 . CD was obtained from Chengdu Must Bio-Technology Co. Ltd. (Chengdu, Sichuan, China), which has been used previously ( 18 , 28 , 29 ). Cells were inoculated in 12-well plates and treated with CD at final concentrations of 0, 10, 20, and 40 µM for 24 h. Protein was collected, and expression levels were monitored by Western blot.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…CD also showed burly binding affinities with S-protein and Mpro proteins from SARS-CoV-2 [ 46 ]. In addition, CD has been found to prevent the expressions of FURIN, TMPRSS2 and CTSL, the SARS-CoV-2 receptors, on cancer cell lines in dose dependent manners [ 34 , 47 , 48 ]. m 6 2 A, as a modified ribonucleoside [ 49 ], was also reported to inhibit the expressions of CTSL on cancer cells in dose dependent manners [ 47 ].…”
Section: Discussionmentioning
confidence: 99%